PENGARUH EFEKTIVITAS PRAKTIK PENGUNGKAPAN RISIKO TERHADAP VOLATILITAS RETURN SAHAM DAN NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015 – 2017) - Antania Fortuneysa; Andrian Budi Prasetyo (Diponegoro Journal of Accounting, 2019)
This study investigates the association between the effectiveness of risk disclosure practices, stock return volatility, and firm value. The independent variables is the effectiveness of risk disclosure practices, measured using a risk disclosure index for insurers. Stock return volatility, and firm value are the dependent variables of this study. The result shows that corporate risk disclosure has a negative effect in the stock return volatility and financial crisis has not significant in moderating the relationship between risk disclosure and stock return volatility. Then, corporate risk disclosure has a positive effect on firm value.